On the Growth and Reproductive Biology of asp, Aspius vorax, Population from the Middle Reaches of Euphrates River - Saleh, Fayez Al; Hammoud, Vienna; Hussein, Abdulrazak; Alhazzaa, Ramez (My University, 2012)
Endemic asp, Aspius vorax, from the middle section of the Euphrates River flowing through eastern Syria were studied to determine the main characteristics of their population structure, morphological parameters and reproductive biology. Samples ranged between 0+ and 4+ years of age and were dominated by 2+ years old group. Total length (TL) ranged between 19 and 70 cm corresponding with 46 to 2824.5 g weight, respectively. Fish growth has isometric pattern and the overall sex ratio was unbiased. Seasonal changes in the condition factor were related with the water temperature as well as the spawning season. Annual cycle of gonadosomatic index (GSI) readings indicated that spawning season occur around March when fish longer than 36 cm can mate. Average pre-spawning GSI was greater in individuals older than 2 years. Meanwhile, female fecundity was highly related to TL and weight. These findings did not always concur with previous observations from other asp populations, mainly in southern and northern Mesopotamia. Our results highlighted basic biological aspects of the local population and indicated differences between populations which can assist in fisheries management, conservation and commercial culture of the investigated species.
Keywords: Aspius vorax; growth; Syria; reproduction; morphological properties; Euphrates